Mortality among persons with tuberculosis in Zambian hospitals: A retrospective cohort study. - Josphat Bwembya; Ramya Kumar; Victoria Musonda; Rhehab Chimzizi; Nancy Kasese-Chanda; Lameck Goma; Mushota Kabaso; Reford Mihova; Sulani Nyimbili; Vimbai Makwambeni; Soka Nyirenda; Alwyn Mwinga; et al. (Public Library of Science (PLoS), 2024)
Tuberculosis (TB) mortality in Zambia remains high at 86 per 100,000 populations, translating to approximately 15,000 TB-related deaths annually. We conducted a nationwide retrospective cohort study to understand predictors, time to death, and probable causes of mortality among persons on TB treatment in Zambia. We reviewed medical records for persons with TB registered in 54 purposively selected hospitals in Zambia between January and December 2019. We fitted a Cox proportional hazards model to identify predictors of mortality. Of the 13,220 records abstracted, 10,987 were analyzed after excluding records of persons who transferred in from other hospitals, those with inconsistent dates and those whose treatment outcome was not evaluated. The majority of persons with TB were men, (61.5%, n = 6,761) with a median age of 36 years (IQR: 27-46 years). Overall, 1,063 (9.7%) died before completing TB treatment (incidence rate = 16.9 deaths per 1,000 person-months). Median age at death was 40 years (IQR: 31-52). The majority of deaths (75.7%, n = 799) occurred in the first two months of TB treatment, with a median time to death of 21 days (IQR: 6-57). Independent risk factors for TB mortality included age >54 years, being treated in Eastern, Southern, Western, Muchinga and Central provinces, receiving treatment from a third-level or mission hospital, methods of diagnosis other than Xpert MTB/RIF, extrapulmonary TB (EPTB), and positive HIV status. Probable causes of death were septic shock (18.8%), TB Immune Reconstitution Inflammatory Syndrome (TB IRIS) (17.8%), end-organ damage (13.4%), pulmonary TB (11.4%), anemia (9.6%) and TB meningitis (7.8%). These results show high mortality among people undergoing TB treatment in Zambia. Interventions targeted at persons most at risk such as the elderly, those with EPTB, and those living with HIV, can help reduce TB-related mortalities in Zambia.